Long Term Impact in Reinforced Recycled Concrete Beams Under 9-Month Loading - Oad, M.; Buller, A. H.; Memon, B. A.; Memon, N. A.; Sohu, S. (Engineering, Technology & Applied Science Research, 2019)
Green concrete is an active area of research. Structural demolishing waste is a global serious problem, particularly in urban areas. This research paper presents the experimental evaluation of the effect of long term loading on reinforced green concrete beams. Three beams were cast with partial replacement of natural coarse aggregates with demolished old concrete. Three beams were cast with all-natural coarse aggregates to compare the results. The beams were mounted on purpose made frames for 9 months. Deflection, strain and cracking in beams were monitored on a daily basis. After 9 months, the beams were tested until failure in a universal load testing machine under central point load. It was observed that the proposed beams exhibited 3.55% reduction in maximum load caring capacity compared to control specimens. The obtained results show good performance of the proposed green concrete beams under 9-month long term loading.